The Role Of Artificial Intelligence In Developing Teaching Skills Among Gifted School Teachers (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This study aimed to identify the role of artificial intelligence (AI) in developing the teaching skills of teachers in schools for gifted students and to examine differences according to academic qualification, years of experience, and participation in AI-related training courses. The study adopted a descriptive research design. The sample consisted of 87 teachers from schools for gifted students in Lattakia Governorate. Data were collected through a questionnaire comprising 25 items covering three teaching skill domains: planning, implementation, and assessment. The results showed that the role of AI in developing teaching skills was moderate overall. Significant differences were found according to academic qualification, with teachers holding postgraduate degrees demonstrating greater ability to employ AI technologies in enhancing their teaching skills. The findings suggest that higher academic qualifications contribute to more effective use of AI applications in educational practice. The study also revealed that teachers who had received AI-related training were more proficient in utilizing intelligent technologies. They demonstrated stronger skills in analyzing educational content, formulating instructional objectives, and integrating interactive activities and AI-supported educational software during teaching. In contrast, no statistically significant differences were found according to years of teaching experience.
Keywords: Artificial intelligence, teaching skills, gifted schools